THE TEACHERS' CLINIC. - Carson, A. B.; Marple, Raymond P.; Perry, K. W.; Mautz, R. K.; Seiler, Robert E.; Dunn, Clarence L. (The Accounting Review, 1956)
Abstract The article presents matters related to accounting for students of accounting. The students of today will be the practitioners of tomorrow. One of these is the trend toward a constantly increasing proportion of fixed to total costs. The article presents theory cases for undergraduate courses. After some examination, the writers have found a means of achieving, in part, some of these goals. In a two-hour undergraduate course called "Current Accounting Topics," an effort is made to give students something other than conventional text-book material and to encourage the discussion of matters of theory in a framework that differs from the usual problem-solving approach. The article also presents a simplified three variance technique. The basic concepts involved in calculating the three components that make up the difference between manufacturing expenses incurred and the amount that is charged to production under a standard cost system are difficult matters for most students of cost accounting. The article describes about helping accounting students to learn how to analyze a business transaction.